Fischbestandsuntersuchungen im atlantischen Sektor der Antarktis im Januar/Februar 1985 - Kock, K.-H. (1985)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010